The diagnosis of asymptomatic disease is associated with fewer healthy days: A cross sectional analysis from the national health and nutrition examination survey. Issue 1 (28th September 2018) - Hanmer, Janel; Yu, Lan; Li, Jie; Kavalieratos, Dio; Peterson, Laurel; Hess, Rachel
Abstract : Objective: To examine the effect of the diagnosis of asymptomatic disease on health‐related quality of life (HRQoL). Design: Secondary analysis of a national data set. Method: We analysed adult participants in the 2011–2012 National Health and Nutrition Examination Survey (NHANES) of the civilian non‐institutionalized US general population. Across three asymptomatic diseases (glucose intolerance, hyperlipidaemia, and hypertension), we examined four groups (without disease; with disease but no diagnosis; with disease and diagnosis but no treatment; and with disease, diagnosis, and treatment). For each asymptomatic disease, we examined group differences in self‐rated health (ordinal logistic regression) and Healthy Days outcomes (number of the last 30 days that physical health was not good, mental health was not good, or inactive; regression). Models were adjusted for age, sex, smoking status, insurance status, income, education, race, body mass index, and comorbid conditions. Results: Analyses included 6012 respondents (glucose intolerance), 2772 respondents (hyperlipidaemia), and 5524 respondents (hypertension). In adjusted models, those who did not know about their disease had the same self‐rated health scores as those without the disease, those with the disease without treatment, and those with disease and treatment. In adjusted analyses of the Healthy Days questions, those with unknown disease reported the same number of unhealthy days as those without disease with the exception of glucose intolerance. Conversely, in four of the nine possible comparisons, those with known disease without treatment reported more unhealthy days than those with who did not know about their disease. Conclusions: In adjusted analyses, individuals knowing about their asymptomatic disease are more likely to experience decrements in healthy days compared to those without knowledge of their asymptomatic disease. Statement of contribution What is already known on this subject? There has been sparse evidence that diagnosis of asymptomatic diseases is related to reduced health‐related quality of life in population studies. Previous studies have included patients receiving treatment, which impedes the ability to isolate the effects of diagnosis from the effects of treatment. What does this study add? This report examines three asymptomatic health conditions: glucose intolerance, hyperlipidaemia, and hypertension. Those who did not know about their health condition generally had the same health‐related quality of life scores as those without health conditions. Conversely, those diagnosed with disease but not receiving treatment reported worse health‐related quality of life.